Acer okamotoanum and isoquercitrin improve cognitive function via attenuation of oxidative stress in high fat diet- and amyloid beta-induced mice. Issue 10 (2nd October 2019) - Kim, Ji Hyun; Lee, Sanghyun; Cho, Eun Ju
Abstract : High fat diet (HFD) and accumulation of amyloid beta (Aβ) are known as a risk factor of Alzheimer's disease. Acer okamotoanum and isoquercitrin improved cognition function against both HFD and Aβ accumulation by inhibiting oxidative stress. Abstract : Obesity induced by high-fat diet (HFD) and accumulation of amyloid beta (Aβ) are known as a risk factor of Alzheimer's disease. We previously identified isoquercitrin (IQ) as an active compound of Acer okamotoanum . In the present study, we investigated the protective effects of the active ethyl acetate (EtOAc) fraction from A. okamotoanum and IQ on HFD and Aβ25–35 -induced cognitive impairment mice. C57BL/6J mice were fed with HFD for 10 weeks and then Aβ25–35 was injected intracerebroventricularly (i.c.v.). The EtOAc fraction of A. okamotoanum and IQ were administered orally for 4 weeks at 100 and 10 mg kg −1 day −1, respectively. Learning and memory functions were evaluated using behavioral tests including T-maze, object recognition and Morris water maze tests. The HFD and Aβ25–35 injection significantly impaired cognitive and memory function. However, administration of A. okamotoanum and IQ improved spatial cognitive ability and object recognition ability in T-maze and novel object recognition tests. In addition, A. okamotoanum and IQ-administered groups showed enhanced learning and memory function compared with HFD and Aβ25–35 -induced cognitive impairment mice in the Morris water maze test. Furthermore, administration of A. okamotoanum and IQ attenuated oxidative stress in the brain via inhibition of reactive oxygen species production, lipid peroxidation, and nitric oxide formation. Therefore, we suggest that A. okamotoanum and IQ improve HFD- and Aβ25–35 -induced cognitive impairment by inhibition of oxidative stress, and A. okamotoanum and IQ might be potential candidates for prevention and treatment of obesity- and Aβ-induced cognitive impairment.